(untitled) (Ciencia Veterinaria, 2017)
Haemonchus spp. larva III were exposed to different concentrations of hydro-alcoholic extract of native and naturalized plant of La Pampa province,with the objective to evaluate the larvicidal effect. The vegetable extracts were provided by the plant extract bank of the research and development centre (CIDEF) of the Faculty ofVeterinary Medicine at the National University of La Pampa. The Haemonchus spp. was cultured from faces of infected ovine maintained in confinement to avoid contamination.The larvas were provided by the Parasitology and Parasitic Diseases course at the Faculty of Veterinary Medicine at the National University of La Pampa. Out of 53 vegetable hydroalcoholic extract proven, 20 inhibit completely the larva motility, 18 have hardly effect and 15 did not have any effect